Future directions for notifiable diseases: tuberculosis-related laws in the Philippines - Yuri Lee (Globalization and Health, 2018)
Abstract Background With the increasing burden of tuberculosis (TB) in the Philippines, and the risk of multidrug resistance to TB, there is a need to strengthen the surveillance system. In many countries, cases of TB are reported to health authorities, and reporting is an effective way to manage TB. Although TB is a universal and representative reportable disease, the Philippines does not designate it as a notifiable disease. Main text This study aimed to review and compare current communicable disease-related laws and regulations in the Philippines with relevant international laws and regulations in other countries, to highlight where current TB notification regulations require change, or to determine whether they reflect global trends. Furthermore, we aimed to have TB included along with other communicable diseases on the list of legally required notifiable diseases in the Philippines. We reviewed current TB-related laws, acts of parliament, executive orders, presidential decrees, administrative orders, and memorandums. We undertook a literature review of relevant World Health Organization documentation, with 17 countries selected for comparison. Data on reported TB cases in the Philippines were obtained from health authorities, and health legislation data from foreign countries was collected from a public law database or from the government websites of each country. Most of the selected countries have a legislative basis for regulating notifiable diseases. In many countries, including Australia, Canada, China, Kiribati, Nauru, Niue, New Zealand, the Republic of Korea, Singapore, the United Kingdom, and Vanuatu, laws on communicable disease notification include TB notification. Our results suggest that notification of communicable diseases should be enforced through domestic health legislation. Conclusion To align the Philippines with standard practice in the selected countries, TB could be included on the list of notifiable diseases in one of two ways. First, the current regulation “Revised List of Notifiable Diseases, Syndromes, Health-related Events and Conditions of 2008” could be revised to include TB. Second, new TB regulations could be introduced and implemented. Any revisions or new regulations should specify methods to identify and manage TB, and safeguard individual rights.